Hydrogen production from CH4 dry reforming over Sc promoted Ni / MCM-41. (2nd August 2019) - Al-Fatesh, Ahmed S.; Atia, Hanan; Abu-Dahrieh, Jehad K.; Ibrahim, Ahmed A.; Eckelt, Reinhard; Armbruster, Udo; Abasaeed, Ahmed E.; Fakeeha, Anis H.
Abstract: The activity of Ni supported on MCM-41 catalyst with/without scandium promoter was investigated for hydrogen production. The performance of the catalysts with different Sc loadings (0.00, 0.10, 0.25, 0.50, 0.75, 1.00 and 3.00 wt%) was examined. N2 adsorption-desorption, X-ray diffraction (XRD), temperature-programmed reduction (TPR), thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used for the characterization of the catalytic materials. The prepared catalysts were tested in dry reforming of methane. The effect of Sc addition on activity, hydrogen yield, H2 /CO ratio and stability are discussed. CH4 and CO2 conversions were measured under atmospheric pressure at 800 °C. Low Sc loading (<0.75 wt%) showed a positive effect on H2 yield, CH4 and CO2 conversions. Addition of Sc strengthened the interaction of Ni with support and also increased the basicity which in turn affected the amount of CO2 adsorbed on the surface of the catalyst. Notably, promoting with Sc almost suppressed the carbon formation leading to outstanding catalytic stability; thus 17% carbon deposition reduction was attained. The effect of different reaction temperatures, GHSV and CH4 :CO2 ratio was also investigated. Highlights: Mesoporous Ni/MCM-41 samples promoted with scandium have higher activity and stability. Sc is an effective promoter that assists Ni dispersion. Low Sc content (0.1–0.75) suppressed the coke deposition. Sc promoter increased the selectivity to H2 /CO ratio toward the unity.